What's new in nutrition for adults with diabetes?. Issue 3 (March 2016) - Nwankwo, Robin; Funnell, Martha
Abstract : Patients with diabetes often get conflicting advice on how to plan meals in order to reach their glycemic targets and weight goals. Implement these evidence-based guidelines to set them on the path to personalized nutrition.